2011
DOI: 10.1029/2010wr009582
|View full text |Cite
|
Sign up to set email alerts
|

The role of land use and soils in regulating water flow in small headwater catchments of the Andes

Abstract: [1] Land use changes can have a significant impact on the terrestrial component of the water cycle. This study provides a comparison of three small headwater catchments in the Andean mountains of Colombia with different composition of land use. Several methods were used to quantify differences in the hydrological behavior of these catchments such as flow duration curves, stormflow analysis, and the linear reservoir concept. They were combined with an analysis of the characteristics of soils that contribute to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
84
2
8

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(100 citation statements)
references
References 39 publications
(38 reference statements)
6
84
2
8
Order By: Relevance
“…No âmbito da região da Serra da Mantiqueira, Menezes et al (2009) Esses resultados encontram sustentação em trabalhos recentes, como os de Bonell et al (2010), Roa-Garcia et al (2011) e Hümann et al (2011, os quais estudaram o comportamento da condutividade hidráulica sob condições de Floresta Nativa nos Andes colombianos, no sudoeste da Alemanha e no oeste da Índia, respectivamente. Nesses trabalhos, ficou constatado que a presença de florestas nativas, em avançado estádio de desenvolvimento (floresta madura), propicia condições para a gênese de poros gravitacionais com altos valores de porosidade drenável e condutividade hidráulica saturada, com a formação de fluxos preferenciais.…”
Section: Mapeamento Do Iqs Ra Na Bacia Hidrográfica Do Alto Rio Grandeunclassified
See 1 more Smart Citation
“…No âmbito da região da Serra da Mantiqueira, Menezes et al (2009) Esses resultados encontram sustentação em trabalhos recentes, como os de Bonell et al (2010), Roa-Garcia et al (2011) e Hümann et al (2011, os quais estudaram o comportamento da condutividade hidráulica sob condições de Floresta Nativa nos Andes colombianos, no sudoeste da Alemanha e no oeste da Índia, respectivamente. Nesses trabalhos, ficou constatado que a presença de florestas nativas, em avançado estádio de desenvolvimento (floresta madura), propicia condições para a gênese de poros gravitacionais com altos valores de porosidade drenável e condutividade hidráulica saturada, com a formação de fluxos preferenciais.…”
Section: Mapeamento Do Iqs Ra Na Bacia Hidrográfica Do Alto Rio Grandeunclassified
“…Entretanto, esses índices não captam a influência do uso do solo nos atributos de superfície associados à infiltração de água, o que, em condições tropicais e subtropicais, são mais relevantes do que indicadores baseados apenas da paisagem. Um exemplo fundamental dessa situação consiste da influência de matas nativas no comportamento hidrológico de bacias hidrográficas de cabeceira (Bonell et al, 2010;Roa-Garcia et al, 2011). Nessa linha, Menezes et al (2009) buscaram analisar o comportamento hidrológico de duas nascentes em função das características pedológicas do Cambissolo na região da Serra da Mantiqueira.…”
Section: Introductionunclassified
“…The authors found higher rates of stream discharge during precipitation events in the catchment with a higher percentage of grazed grassland, which is explained by compaction of soils. On the long time scale they found differences in the MTTs, which they ascribe to the difference in vegetation cover/land use, notably the occurrence of wetlands and forests which increased MTTs due to an increased water holding capacity (Roa-Garcia, 2009). Darling and Bath (1988) measured more negative δ 18 O values in the percolate of a lysimeter compared to soil water samples of drill cores from the same depth.…”
Section: Introductionmentioning
confidence: 99%
“…Soils are mainly andosols, based on the FAO classification (Gardi et al, 2014), derived from volcanic material characterized by their high soil moisture (Buytaert et al, 2005a) and water retention capacity (Janeau et al, 2015;Roa-García et al, 2011). In 45 addition, studies in the area describe an elevated amount of organic carbon and mineralogical composition in the soil of the páramos at lower catchments, which decreases with altitudinal gradient (Minaya et al, 2015).…”
Section: Locationmentioning
confidence: 99%